Critical Synthesis Package: UCLA Geriatrics Attitudes Scale - Maria van Zuilen (Association of American Medical Colleges, 2015)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the UCLA Geriatrics Attitudes Scale (GAS); and (2) a copy of the GAS with the scoring key developed by David B. Reuben, MD and Ming Lee, PhD. The GAS is a 14-item scale developed to assess health care providers' attitudes toward older persons and caring for older patients. The instrument contains five positively and nine negatively worded statements that are rated on a scale from 1 (strongly disagree) to 5 (strongly agree) with 3 representing a neutral rating. Scores on the negatively worded items are reversed when calculating the total score. The GAS is easy to administer and score. The initial population studied was primary care residents but it has since been used with a broad range of health profession trainees and practitioners. Its main use has been to assess the effectiveness of educational interventions in improving attitudes, but researchers have also used the scale to determine correlates and potential predicators of positive attitudes. The initial study provided modest evidence of the scale's internal consistency (Cronbach's alpha of 0.76) and supplied evidence for other validity indicators. A factor analysis in a later study by the same group revealed four domains. However, subsequent studies have not been able to consistently replicate these findings and have brought to light significant validity concerns. Few studies have reported a post-intervention improvement and the magnitude of the improvements have been small, raising the question of practical significance. Post-intervention improvements should be interpreted with caution as evidence suggests this scale may be measuring more than just attitudes. The scale may be of interest to educators and educational researchers in the health care field. However, potential users should carefully consider validity concerns.